Synergistic effect of endogenous gluten and oleic acid on wheat starch digestion by forming ordered starch-fatty acid-protein complexes during thermal processing - Jing Du; Meng-yao Lv; Hai-long Zhang; Shen-sheng Xiao; Shuang-yi Zheng; Xue-dong Wang (Current Research in Food Science, 2023)
The aim of this study was to understand the potential of endogenous gluten inhibiting the digestibility in vitro of wheat starch (WS) in starch-fatty acid-protein system. Therefore, the influences of gluten and whey protein isolate (WPI) on the properties, multi-scale structure and in vitro digestibility of WS in WS-oleic acid (OA)-protein system were compared. The results of digestibility in vitro indicated that the ternary system of starch-fatty acid-protein showed higher resistant starch (RS) content as well as lower rapidly digestible starch (RDS) content than the binary system of WS-OA, demonstrating protein decreased WS digestion of WS-OA system. The results of pasting properties showed that gluten and WPI both increased the viscosities of WS-OA system during the cooling period due to the formation of WS-OA-protein ternary complex. The results of swelling power and solubility analysis showed that gluten and WPI both decreased the swelling power and solubility of WS-OA binary system. Laser Confocal Raman and X-ray diffraction (XRD) studies indicated that gluten and WPI both increased the ordered degree of WS-OA binary system by decreasing the full width at half maximum (FWHM) of the peak at 480 cm−1 and increasing crystallinity degree. Strikingly, compared with WPI, gluten had greater effects on the digestibility in vitro, pasting properties and ordered degree of WS in WS-OA-protein system. Therefore, gluten as an endogenous protein has the potential application in reduction the enzymatic digestibility of WS by regulating the reassembly of starch and fatty acid during thermal processing.